Host Generated siRNAs Attenuate Expression of Serine Protease Gene in Myzus persicae - Bhatia, Varnika; Bhattacharya, Ramcharan; Uniyal, Prem L.; Singh, Rajendra; Niranjan, Rampal S. (PLOS ONE, 2012)
Background Sap sucking hemipteran aphids damage diverse crop species. Although delivery of ds-RNA or siRNA through microinjection/feeding has been demonstrated, the efficacy of host-mediated delivery of aphid-specific dsRNA in developing aphid resistance has been far from being elucidated. Methodology/Principal Findings Transgenic Arabidopsis expressing ds-RNA of Myzus persicae serine protease (MySP) was developed that triggered the generation of corresponding siRNAs amenable for delivery to the feeding aphids. M. persicae when fed on the transgenic plants for different time intervals under controlled growth conditions resulted in a significant attenuation of the expression of MySP and a commensurate decline in gut protease activity. Although the survivability of these aphids was not affected, there was a noticeable decline in their fecundity resulting in a significant reduction in parthenogenetic population. Conclusions/Significance The study highlighted the feasibility of developing host based RNAi-mediated resistance against hemipteran pest aphids.